Strategi Adaptif Tutor dalam Mengimplementasikan Prinsip Andragogi pada Pendidikan Kesetaraan Paket C di PKBM Budi Utama Surabaya - Andhini, Revalina Nurasita; Nugroho, Rivo (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: Nonformal equivalency education requires teaching practices that can respond to adult learners’ heterogeneous educational histories, responsibilities, learning readiness, and practical needs. This study examines how a tutor adapts instruction while applying andragogical principles in the Package C equivalency program at PKBM Budi Utama Surabaya. A qualitative case-study design was employed. Five informants were purposively involved: one PKBM administrator, one Package C biology tutor, and three learners representing grades 10, 11, and 12. Data were generated through classroom observation, in-depth interviews, and documentation, then analyzed using the interactive model of data collection, condensation, display, and conclusion drawing. The findings indicate that adaptive tutoring was enacted through five interrelated practices: adjusting teaching methods to learner readiness; contextualizing materials using familiar examples; encouraging participation through questioning, tasks, and direct interaction; combining worksheets, tutor explanations, and personal digital devices as learning resources; and maintaining flexibility in pacing, time, and communication. The evidence also shows that institutional support, class organization, face-to-face interaction, and learner engagement facilitated adaptation, whereas differences in academic ability, limited learning time, and the need for repeated explanation constrained implementation. The study argues that adaptive tutoring is not merely methodological variation but a practical mechanism that translates andragogical principles into the everyday realities of equivalency education. These findings strengthen the role of tutors as responsive facilitators in nonformal adult-learning settings and highlight the need for institutional support for contextual, participatory, and flexible learning. Abstrak: Pendidikan kesetaraan nonformal membutuhkan praktik pembelajaran yang mampu merespons keragaman riwayat pendidikan, tanggung jawab kehidupan, kesiapan belajar, dan kebutuhan praktis warga belajar dewasa. Penelitian ini menganalisis strategi adaptif tutor dalam mengimplementasikan prinsip andragogi pada pembelajaran Pendidikan Kesetaraan Paket C di PKBM Budi Utama Surabaya. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Lima informan dipilih secara purposif, terdiri atas satu pengelola PKBM, satu tutor Biologi Paket C, dan tiga warga belajar yang mewakili kelas 10, 11, dan 12. Data diperoleh melalui observasi pembelajaran, wawancara mendalam, dan dokumentasi, kemudian dianalisis menggunakan model interaktif berupa pengumpulan data, kondensasi data, penyajian data, serta penarikan dan verifikasi kesimpulan. Hasil penelitian menunjukkan lima bentuk strategi adaptif yang saling berkaitan, yaitu penyesuaian metode terhadap kesiapan warga belajar, kontekstualisasi materi melalui contoh yang dekat dengan kehidupan, penguatan partisipasi melalui tanya jawab dan tugas, penggunaan kombinasi lembar tugas, penjelasan tutor, dan gawai sebagai sumber belajar, serta fleksibilitas tempo, waktu, dan komunikasi. Dukungan lembaga, pembagian kelas, interaksi tatap muka, dan keterlibatan warga belajar mendukung proses adaptasi, sedangkan variasi kemampuan akademik, keterbatasan waktu, dan kebutuhan pengulangan penjelasan menjadi hambatan. Penelitian ini menegaskan bahwa strategi adaptif bukan sekadar variasi metode, melainkan mekanisme praktis yang menjembatani prinsip andragogi dengan realitas pembelajaran pendidikan kesetaraan.